Moving assemblies. Socio-political mobilization in Angola’s collective transport - Neto, P. F. (Cultural Studies, 2020)
The authoritarian regime in Angola seeks to control every dimension of life in the country interfering with a set of fundamental rights such as the freedom of assembly, of movement and of expression. However, by their very fluid nature, by the inherent massing and anonymity, the contexts of mobility not only offer a set of social interactions rarely allowed in the current political panorama, but also provide an escape to effective surveillance and monitoring from authorities. Furthermore, the multidirectional encounters that mobility enacts — with people, situations, events, spatial mnemonics — create the conditions for the acknowledgement of an individual and collective plight. The absence of a likely public space for the discussion of certain compelling issues transforms the contexts of mobility into ephemeral moving assemblies, into unconventional sites of resistance where a sociopolitical culture is hatching. Collective transport's ambiguous anthropological qualities configure a highly productive ethnographic setting for the surreptitious researcher and an inescapable context if one is to assess Angola’s current reality. By depicting the social life of Angola’s public transport I will unveil the several mechanisms and possibilities behind these moving assemblies examining how mobility and sociopolitical mobilization intertwine.